Consolidating the Continental Drift: American Influence on Diefenbaker’s National Oil Policy - Nemeth, Tammy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2002)
AbstractThe National Oil Policy of 1961 provides an opportunity to re-assess the nature of Prime Minister John Diefenbaker's attitudes towards the United States, usually characterised as hostile. A central feature of this oil policy, that an oil pipeline from Alberta would not extend east of the Ottawa River, necessitated an increase in oil imports from the US, thereby strengthening the continental pull of the energy trade. It is argued that Diefenbaker's amicable relationship with President Eisenhower was an essential factor in the policy decision, and it was not until John F. Kennedy became president that the relationship shifted. Diefenbaker was not anti-American, but counter-Kennedy.